2018
DOI: 10.2147/tcrm.s147164
|View full text |Cite
|
Sign up to set email alerts
|

Triplet CFTR modulators: future prospects for treatment of cystic fibrosis

Abstract: Cystic fibrosis (CF) is an autosomal recessive genetic disease characterized by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR is a chloride channel responsible for ion flow across epithelial surfaces of lung, sinuses, pancreas, intestine, and liver. Researchers have grouped CFTR genetic mutations into various protein defects: reduced protein synthesis (class 1 mutations), abnormal protein folding and maturation (class 2 mutation), and abnormal gating (class 3 mutation). Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
0
32
0
2
Order By: Relevance
“…Several next-generation correctors are in development for use in triplet combination therapies for CF [ 22 ]. In a phase 3 trial in subjects with one F508del mutation and one minimal function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several next-generation correctors are in development for use in triplet combination therapies for CF [ 22 ]. In a phase 3 trial in subjects with one F508del mutation and one minimal function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an unmet need for treatment combinations with improved efficacy and safety profiles, and scientific rationale for using combinations of correctors with differing mechanisms or sites of action in novel doublet and triplet combinations, due to potential additive or synergistic effects [ 20 , 21 ]. At the time that this study was conducted, there were a number of novel correctors at various stages of development, including but not limited to C1-type correctors (GLPG/ABBV-2222, lumacaftor, and tezacaftor), C2-type correctors (VX-659 and VX-445), and third-generation correctors (PTI-801) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…CF remains incurable up until today, but the development of CFTR modulators has increased the prospects that CF disease manifestation might be stalled or even prevented, in the near future [21] . Two phase 2 clinical trials have shown that the efficacy of the newest triple combination therapy exceeds the efficacy of the previous developed combinations, but is still only accessible for pa- tients with particular CFTR mutations [ 22 , 23 ].…”
Section: Body Of Textmentioning
confidence: 99%
“…The barrier function of TJs is regulated by different mechanisms in various tissues. Cystic fibrosis is induced by the dysfunction of cystic fibrosis transmembrane conductance regulator (CFTR), a cyclic AMP-activated chloride channel located in the apical membrane of the secretory epithelium of airways, the intestine, bile ducts, and the epididymis [ 33 , 34 ]. The PDZ domain of CFTR interacts with ZO-1 to regulate cell proliferation and differentiation via the ZO-1/ZONAB pathway.…”
Section: Phase Separation As a Potential Targetmentioning
confidence: 99%